The accumulation and compartmentalization of isometamidium chloride in Trypanosoma congolense, monitored by its intrinsic fluorescence - Wilkes, J.M.; Peregrine, A.S.; Zilberstein, D. (1995)
Interaction of the trypanocide isometamidium chloride with components of Trypanosoma congolense results in characteristic shifts in the intrinsic fluorescence of the drug. The specificity of this interaction was investigated by analysing the effects of various physiochemical manipulations on its fluorescence properties. The characteristic shifts involved a preferential increase in the intensity of one emission peak over the over, resulting in a systematic increase in the ratio of fluorescence intensities. These effects were apparently due to constraints on fluorophore free rotation in the solution (that is, viscosity). Purified DNA produced similar effects in a saturable manner displaying high affinity for the drug, indicating that the constraint involves binding of the drug to high-affinity binding sites within the DNA. Such binding sites were demonstrated in lysates derived from trypanosomal cells. The binding sites were associated with macromolecular species (Mr>12000), and were partly disrupted by thermal denaturation and proteolysis. Treatment with DNase 1 produced high levels of disruption of the binding sites (>85 percent), indicating an involvement of DNA in the binding. BSA demonstrated weak non-specific binding of the drug. Entry of drug into live trypanosomal cells (monitored by 14C-labelled drug uptake) was paralleled by fluorescence shifts observed under comparable conditions of drug concentration and buffer conditions. Both systems (fluroescence shifts and accumulation of labelled drug) indicated the presence of a saturable membrane transporter with high affinity for the drug. We conclude that monitoring the fluorescence shifts of isometamidium constitutes a sensitive and highly specific probe for entry of the drug into trypanosomal cells, thereby enabling resolution of the transport events involved.